Rancang Bangun Plugin Facebook Pada E-Learning Moodle Di SMK Tunas Bangsa Mijen Demak (Information Technology and Telematics, 2015)
ABSTRACT A long with the development of Information Technology, which grew rapidly affect many aspects of life. With the development of the technology world so many social networking sites that affect the public media. Like the facebook site that much-loved almost all societies. As a secondary vocational education institution, SMK Tunas Bangsa Mijen Demak role in the development of science, especially in the field of Information Technology. During this learning process in vocational Tunas Bangsa Mijen Demak still manually, ie the learning process between students and teachers is done with the meeting in the classroom. E-learning is an education system that uses an electronic application to support the development of teaching and learning activities with the media internet, intranet or other computer network media. The purpose of the application design facebook plugin in Moodle e-learning is to facilitate the students or teachers to support the development of teaching and learning in vocational environment Tunas Bangsa Mijen Demak. Make it easy for teachers to present course material and assignments which will be shared to facebook. Keywoard: e-learning moodle aplication, plugin facebook.